The European Monetary Union : Europe at the crossroads - Acocella, Nicola, 1939- (Cambridge : Cambridge University Press, 2020)
The European Union is at a crossroads. This book analyzes the historical roots of the EU's monetary and financial institutions in order to better understand its struggle to maintain an economic and monetary union, as well as the ongoing problems facing the Euro. The institutions of the EU are based on the operation of free markets, a common monetary policy, and the European Central Bank. These founding policies have created many of the imbalances at the root of the ongoing European recession. Reemerging threats of populism and localism are poised to further disintegrate the European construction and may spark fierce opposition between countries. Acocella engages with these risks, suggesting detailed actions for reform within the EU and its institutions that may steer it away from further conflict, allowing it to better serve its member states and citizens.
Title from publisher's bibliographic system (viewed on 07 Sep 2020).
Keywords: Economic and Monetary Union; Monetary unions -- European Union countries; European Union